Carbon Nanomaterials in Biosensors: Should You Use Nanotubes or Graphene - Yang, Wenrong; Ratinac, Kyle R; Ringer, Simon P; Thordarson, Pall; Gooding, J. Justin; Braet, Filip (Angewandte Chemie (International ed.), 2010)
From diagnosis of life-threatening diseases to detection of biological agents in warfare or terrorist attacks, biosensors are becoming a critical part of modern life. Many recent biosensors have incorporated carbon nanotubes as sensing elements, while a growing body of work has begun to do the same with the emergent nanomaterial graphene, which is effectively an unrolled nanotube. With this widespread use of carbon nanomaterials in biosensors, it is timely to assess how this trend is contributing to the science and applications of biosensors. This Review explores these issues by presenting the latest advances in electrochemical, electrical, and optical biosensors that use carbon nanotubes and graphene, and critically compares the performance of the two carbon allotropes in this application. Ultimately, carbon nanomaterials, although still to meet key challenges in fabrication and handling, have a bright future as biosensors.